2013
DOI: 10.1159/000350999
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Soft Signs and Brainstem Morphology in First-Episode Schizophrenia

Abstract: Background: Minor motor and sensory deficits or neurological soft signs (NSS) have frequently been reported in patients with schizophrenia at any stage of their illness. NSS have been demonstrated to correlate with neuroanatomical abnormalities in various brain regions. Despite its important role in the integration and coordination of automatic motor actions, the brainstem has so far rather been ignored in previous neuroimaging studies on NSS in schizophrenia. Method: We investigated 21 right-handed first-epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 127 publications
(102 reference statements)
2
25
0
Order By: Relevance
“…Using shape analyses these associations referred to regionally specific morphometric alterations predominantly in the midbrain and pons. Following this line, our findings also correlate well with the study presented by Nopoulos et al (2001), which identified smaller volumes of the midbrain in schizophrenic men and supported the hypothesis that abnormal dopaminergic firing in the midbrain might result in dysregulation of dopamine release in the limbic system and thus worsens the psychotic symptomatology (Hirjak et al, 2013;Nopoulos et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using shape analyses these associations referred to regionally specific morphometric alterations predominantly in the midbrain and pons. Following this line, our findings also correlate well with the study presented by Nopoulos et al (2001), which identified smaller volumes of the midbrain in schizophrenic men and supported the hypothesis that abnormal dopaminergic firing in the midbrain might result in dysregulation of dopamine release in the limbic system and thus worsens the psychotic symptomatology (Hirjak et al, 2013;Nopoulos et al, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…In particular, a previous whole-brain VBM study of our own group in an independent sample found subjects high for the subscale HS to correlate with white matter reductions within the brainstem (Heuser et al, 2011). More recently, our group identified higher scores on the subscales MOCO, COMT, and HS to be associated with volumetric alterations of the brainstem (Hirjak et al, 2013). Using shape analyses these associations referred to regionally specific morphometric alterations predominantly in the midbrain and pons.…”
Section: Discussionmentioning
confidence: 49%
“…Three studies with an overlapping patient cohort of first-episode or recent-onset schizophrenia investigated the association of NSS, which were assessed using the Heidelberg scale, with different morphometric markers. In sum, higher NSS scores were associated with reduced brain stem volume [9] and with changes in cortical thickness in the paracentral gyrus, the postcentral lobule, the precuneus, the inferior parietal lobule, and the temporal lobe [10]. In addition, shape changes in pons and midbrain as well as morphometric alterations of the basal ganglia were found [9,11].…”
Section: Findings Of Neurological Soft Signs From Structural and Funcmentioning
confidence: 91%
“…Neurological function was evaluated by a modified neurological severity score (NSS) [24] on the day before, and on days 7 and 14 after the transplantation. The evaluations consisted of motor (muscle status and abnormal movement), sensory (visual, tactile, and proprioceptive), reflex, and balance tests, and were recorded on a scale of 0-18 (normal score, 0; maximal deficit score, 18).…”
Section: Neurological Behaviormentioning
confidence: 99%